2023
DOI: 10.1186/s12889-023-16649-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrating intimate partner violence prevention content into a digital parenting chatbot intervention during COVID-19: Intervention development and remote data collection

Moa Schafer,
Jamie M. Lachman,
Frances Gardner
et al.

Abstract: Background Intimate partner violence (IPV) is a serious public health issue which experienced a sharp incline during the onset of COVID-19. Increases in other forms of violence, such as violence against children (VAC), have also been linked to the pandemic, and there have been calls for greater prevention efforts that tackle both forms of violence concurrently. The COVID-19 crisis has highlighted the urgent need for evidence-based and scalable violence prevention interventions that target multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Although several studies have shown the benefits of formal, systematic, and repeated training through school-based CSA prevention programs [9][10][11][12][13][14][15][16][17], these school-based CSA prevention programs, which incorporate educational materials such as courses and dramatic performances may not be fully applicable in China because of the lack of systematic education faculty [18], and their preparation and implementation may be impractical due to time and resource constraints in schools [19,20]. Particularly during the COVID-19 pandemic, school-based interventions became unfeasible, emphasizing the importance of remote digital interventions as promising solutions for addressing resource limitations and expanding reach [21][22][23]. Additionally, discussing sexuality in public remains sensitive in China, making it challenging to implement abstract CSA prevention concepts that young children may struggle to comprehend.…”
Section: Introduction Csa Prevalence and Prevention In Chinamentioning
confidence: 99%
“…Although several studies have shown the benefits of formal, systematic, and repeated training through school-based CSA prevention programs [9][10][11][12][13][14][15][16][17], these school-based CSA prevention programs, which incorporate educational materials such as courses and dramatic performances may not be fully applicable in China because of the lack of systematic education faculty [18], and their preparation and implementation may be impractical due to time and resource constraints in schools [19,20]. Particularly during the COVID-19 pandemic, school-based interventions became unfeasible, emphasizing the importance of remote digital interventions as promising solutions for addressing resource limitations and expanding reach [21][22][23]. Additionally, discussing sexuality in public remains sensitive in China, making it challenging to implement abstract CSA prevention concepts that young children may struggle to comprehend.…”
Section: Introduction Csa Prevalence and Prevention In Chinamentioning
confidence: 99%